(untitled) (Research, Society and Development, 2020)
Introduction: The obese individual has a hyper-inflammatory state and metabolic abnormalities related to glycemic metabolism and liver functions that support the hypotheses of greater susceptibility and severity of periodontitis in these patients. However, the biological plausibility for this condition has not yet been established. Objective: To describe the main biological events involved in the relationship between obesity and periodontitis. Material and methods: Theoretical essay based on a systematic review of scientific articles indexed in the PubMed|MEDLINE, Scopus, Embase, Web of Science, Cochrane Library, and bvs|LILACS databases. Results and Discussion: Pro-inflammatory cytokines such as IL-1b, IL-6 and TNF-a, loss of homeostasis between serum leptin and adiponectin levels, as well as increased levels of free fatty acids and reactive oxygen species they seem to exert positive feedback between the deleterious effects of obesity and periodontitis, with an important participation of the liver and insulin resistance in this process, increasing this system more and more. The accumulation of AGEs, increased collagenolysis and vascular complications resulting from hyperglycemia are directly related to the severity of periodontitis and tissue destruction. Oxidative stress participates in this process not only in periodontal tissues but also in the liver, where the functional impairment of this organ is accompanied by an increase in serum levels of C-reactive protein and angiotensinogen, stimulated also by endotoxemia, bacteremia and an increase in serum levels of pro-inflammatory cytokines from periodontal pockets. Conclusion: The effects of obesity on periodontitis seem to be related mainly to the hyperinflammatory state and impaired glucose metabolism.